十三五图 - Yan, Fang (2015)
Presentation by Fang Yan, Deputy Director General, Department of Rural Economy, National Development and Reform Commission, delivered on May 13 at Peking University. The event, “New Normal for Economic Growth, Agriculture, Food and Nutrition Security,” was organized by IFPRI and its co-hosting partners, the Chinese Academy of Agricultural Sciences (CAAS) and National School of Development of Peking University.